Recent Advances in Theory and Application of Dynamical Systems - Zhang, Chunrui (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Dynamical system theory has been widely used to study scientific problems. The purpose of this reprint is to introduce the latest research results related to dynamical system theory. This reprint is a reference for researchers engaged in applied mathematics, biomathematics and related fields.